Maintenance of scorpions of the genus Tityus Koch (Scorpiones, Buthidae) for venom obtention at Instituto Butantan, São Paulo, Brazil - D. M. Candido; S. Lucas (Journal of Venomous Animals and Toxins including Tropical Diseases, 2004)
This work presents the experience of the Laboratory of Arthropods at Instituto Butantan, which maintains scorpions in captivity in order to obtain the venom used in the production of anti-arachnid serum. Between 1993 and 2000, the laboratory received 24.781 specimens of Tityus serrulatus in order to obtain poison for the production of anti-scorpion serum. In the first extraction, performed by electrical stimulation, the animals gave an average quantity of 0.4 mg venom per specimen. Animal acquisition and involved professional safety are considered. In addition, the captivity, handling and feeding techniques are described, as well as the method and equipment used for venom extraction. It shows the importance of regular campaigns, offering information to the general population in order to motivate these to catch and send alive scorpions to the Institute to assuring a regular entrance of scorpions.